Constitutional-legal and socio-economic prerequisites and goals for the creation of federal territories in the Russian Federation and abroad - Starikov, Sergey S. (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право», 2022)
Introduction. The establishment of the possibility of creating federal territories in the Constitution of the Russian Federation and the subsequent adoption of the Federal Law “On the Federal Territory “Sirius” No. 437-FZ of December 22, 2020 make us take a closer look at foreign experience in determining the constitutional legal status, mechanisms of creation and features of functioning of federal territories. Carrying out a comparative analysis will make it possible to predict the prospects for further development of legislation on the creation and identifi cation of the main goals of functioning of federal territories. Theoretical analysis. The review of the types of federal territories and federal districts in the constitutional and legal practice of foreign states allows us to conclude that their creation requires a system of constitutional-legal and socioeconomic prerequisites. The main prerequisites include establishment of the possibility, goals and mechanisms of creation of a federal territory in the Constitution of the state, the defi nition of the spatial and geographical characteristics of the federal territory, as well as the peculiarities of the legal regime of public authority exercised in this territory in the legislation of the state. Empirical analysis. Russia has quite a lot of experience in creating a legal framework for socio-economic, environmental, scientifi c and technological development in individual territories, which was taken into account when creating the Federal Law on Sirius. Results. At present, the main constitutional-legal and socio-economic prerequisites for the creation of new federal territories of Russia have been formed. These prerequisites are of an objective nature and are generally comparable with the experience of foreign countries with the state territorial structure that includes federal territories. The goals of creating federal territories in Russia and foreign countries have their own specifi cs. Abroad, such goals, as a rule, are the special status of the capital, construction of defense structures, environmental protection, and preservation of the specifi cs of the territories where indigenous peoples live. In Russia, the federal territory “Sirius” was created in order to ensure the socio-economic and innovative development of the territory, to increase its investment attractiveness, to preserve the Olympic sports, cultural and natural heritage, to create favorable conditions for identifi cation, self-realization and development of talents, implementation of priorities in scientifi c and technological development of the Russian Federation. In foreign practice, as a rule, the mechanisms for creating federal territories are not used for these purposes, but other socio-economic and organizational-legal instruments are applied.